Studien zu Beethovens Diabelli-Variationen - Münster, Arnold (München Henle Verlag, 1982)
The Diabelli Variations op. 120 are amongst Beethoven's most important piano works. They are the last major composition he wrote for the pianoforte. In this monograph, Arnold Münster writes about the genesis of the work and its lgendary name "Variationen über einen Schusterfleck" (Variations on a cobbler's patch). According to his contemporaries Beethoven is said to have written this above the work himself. Its special place amongst Beethoven's works becomes apparent on establishing the structure of the composition, the connections and similarities with others of his works, on evaluating the compositional technique and on a thorough analysis of the individual variations, based on the available sketches.